1969
DOI: 10.1254/jjp.19.520
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Action of Partial Agonists on the Taenia Caecum of the Guinea Pig and Drug-Receptor Theory

Abstract: In the previous papers (1-3) it has been reported that some partial agonists accelerate the liberation of acetylcholine from the isolated guinea pig and rat ilea to contract them, yet also antagonize the action of the released acetylcholine and that the intrinsic activity (4) or efficacy (5) of a drug is decided by two factors: acetylcholine liberating activity and inhibitory activity to acetylcholine. In this paper, the receptor mechanisms for partial agonists were studied on the ganglion free taenia caecum f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1970
1970
1981
1981

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Furthermore, papaverine and dodecyl trimethylammonium (8), which relaxed the intestinal smooth muscle of the guinea pig, contracted the denervated muscle.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, papaverine and dodecyl trimethylammonium (8), which relaxed the intestinal smooth muscle of the guinea pig, contracted the denervated muscle.…”
Section: Discussionmentioning
confidence: 95%
“…In some experiments, a modified locke Ringer solution was used, in which NaCI and Na HCO, were replaced by KC1 and KHCO3 (5). This modified Locke Ringer solution was called "K-Locke Ringer solution" in this paper.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, some partial agonists in a series of cholinergic drugs contract the isolated taenia caecum (or taenia coli) of the guinea pig and at the same time the contrac tion which they produce is inhibited by their non-secific inhibitory action, so that maximal responses to partial agonists are smaller than that to full agonists (3)(4)(5). Furthermore, ephedrine which was classified as an adrenergic partial agonist relaxes the taenia caecum and at the same time the relaxation which it produces is antagonized by its own excitatory action, so maximal relaxation by it is smaller than that by a full agonist, epinephrine (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dikstein and Sulman (1) postulated that the inhibitory effect of acetone was due to the extraction of phospholipids from the organ, but Ehrenpreis, Hazra and Bigo-Gullino It has been suggested that the mechanism of action of papaverine is concerned with the inhibition of supply of calcium ions to the contractile element of the smooth muscle (9)(10)(11). Sunano and Miyazaki (12) have presented evidence that acetone may induce the change in permeability of calcium ions through the cell membrane of the guinea pig taenia caecum (or taenia coli).…”
Section: Membrane Activitymentioning
confidence: 99%